Dynamics of polynya in the River Ob Bay and predicting of its location - A. V. Popov; N. V. Kubishkin; A. V. Rubchenia; D. V. Drabenko (Лëд и снег, 2016)
Dynamics of the ice edge of (flaw lead) a large polynya in the River Ob Bay was investigated over the period 1997–2016 on the basis of satellite data. More than 800 satellite images were analyzed during the investigation. Relationship between the obtained time series of changing latitude of the ice edge and time series of air temperature, wind and indices of Wangenheim–Girs, the Arctic Oscillation (AO), and North Atlantic Oscillation (NAO) was studied by means of the correlation analysis. The statistical analysis made it possible to reveal that southern position of the ice edge in autumn indicated to warmer winter months. Boundaries of the polynya during every next decade were identically determined by its position during the preceding period, and therewith the pronounced trend of the ice edge shift to south was noticed in 1997–2012. In addition, periodic fluctuations with two different periods were found against the background of trend. During 1996– 2006 the fluctuations were quasi-biennial while after 2006 the period of fluctuations increased up to 4–5 years. Effort to predict the ice edge position aimed at determination of the polynya boundaries in January-February of 2016 was undertaken; data on the air temperature and latitude of the ice edge position for preceding period were used as the predictors. The difference between the prediction and actual data was equal to 0.01 ÷ −0.43 of latitude with the average value for six decades equal to 0.11°. Analysis of inter-annual variability of the edge position indicated that the most close relationship took place with the Vangenheim–Girs index E in May (coefficient of correlation r = −0.73). Maximal values of r exceeding ±0.7 were calculated for the Arctic Oscillation indices in February with a positive shift of one year. When investigating long-term large-scale changes of climatic parameters, analysis of anomalies of average latitude values of the polynya southern boundary had been performed. This allowed to reveal that period of 2005–2006 was a point of inflection. This substantiates the known thesis (conclusion) that a well developed polynya exerts the warming effect on adjacent territories.